2010
DOI: 10.9744/kata.11.2.171-183
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of L1 in EFL Teaching

Abstract: This study is conducted in a classroom action research to improve the students' achievement in writing English sentences in Present Perfect Tense in Structure 1 lessons. The subject consisted of 20 Semester II students who took Structure I lessons in English Education Department of Palangka Raya University, Central Kalimantan, Indonesia. The data were taken from the results of pre test and post test after the action was done. The results show that in cycle 1, in which the explanations were fully in English, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A growing body of research has examined these attitudes and how they are reflected in L1 use in the classroom (Hall and Cook, 2013). Studies have compared L1 attitudes and uses by both the teachers and learners (Hall and Cook, 2013; Leoanak and Amalo, 2018; Littlewood and Yu, 2011; Manara, 2007; Pasaribu, 2001; Storch and Wigglesworth, 2003; Usadiati, 2009; Yulia, 2013), primarily from the teacher’s perspective (Mohebbi and Alavi, 2014; Polio and Duff, 1994; Zacharias, 2004) or mainly from the learners’ viewpoint (Brooks-Lewis, 2009; Macaro, 2005; Scheffler et al., 2017). There is also an emerging body of international research that focusses on how student teachers approach L1 use (Hirsu and Zacharias, 2019) in specific contexts, including Japan (Miura, 2010; Turnbull, 2018), Turkey (Yildiz and Yesilyurt, 2016), and Israel (Orland-Barak and Yinon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has examined these attitudes and how they are reflected in L1 use in the classroom (Hall and Cook, 2013). Studies have compared L1 attitudes and uses by both the teachers and learners (Hall and Cook, 2013; Leoanak and Amalo, 2018; Littlewood and Yu, 2011; Manara, 2007; Pasaribu, 2001; Storch and Wigglesworth, 2003; Usadiati, 2009; Yulia, 2013), primarily from the teacher’s perspective (Mohebbi and Alavi, 2014; Polio and Duff, 1994; Zacharias, 2004) or mainly from the learners’ viewpoint (Brooks-Lewis, 2009; Macaro, 2005; Scheffler et al., 2017). There is also an emerging body of international research that focusses on how student teachers approach L1 use (Hirsu and Zacharias, 2019) in specific contexts, including Japan (Miura, 2010; Turnbull, 2018), Turkey (Yildiz and Yesilyurt, 2016), and Israel (Orland-Barak and Yinon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to Bruen and Kelly (2017), the use of L1 for explaining complex grammatical forms received good feedback from both teachers and students, with teachers seeing it as a "positive resource that can effectively assist the language learning process." Usadiati (2009) found that when Indonesian was utilized with English to explain present perfect tense norms and its impact on writing, there was a greater success rate of 80% as opposed to a 45% success rate. These research results from the literature demonstrate the value of L1 as a tool for enhancing grammar learning.…”
Section: Teaching Grammarmentioning
confidence: 99%
“…NOVEMBER 2023E-ISSN. 2721 language in the classroom impacting in depriving students' chance in practice the oral skills (Sener and Korkut 2017) In the contrary some research revealed that the use if first language in proper portion can affecting on the improvement of students' achievement in writing sentences (Usadiati 2010) and leading students' achievement (Damra, Heba Mohammad, and Mahmoud Al Qudah 2012).…”
Section: The Use Of First Language In Foreign Language Classroommentioning
confidence: 99%